Effect of inulin and whey protein concentrate on the physicochemical properties and shelf life of reduced‐fat cream puffs. Issue 12 (12th August 2022) - Onsri, Narudee; Hudthagosol, Chatrapa; Sanporkha, Promluck
Abstract: This study used inulin at 20, 35, and 50% and whey protein concentrate (WPC) at 5, 10, and 15% in crust (CPC) and filling (CPF) of cream puffs. Addition of inulin and WPC significantly decreased the viscosity and specific volume. Using inulin at 20% retained a defined structure of CPC. In sensory evaluation, 20% inulin and 10% WPC formula received the highest scores of appearance and taste among the formulas. For CPF, too high viscosity was found in treatment using inulin at 35 and 50%. The panelists rated the 20% inulin and 5% WPC highest in texture, taste, odor, and overall acceptability. Thus, developed formula could reduce total energy from fat and increase 90% of dietary fiber and 19% of protein. Inulin and WPC were successfully used as fat replacers to extend shelf life of the storage times from 9 to 13 days while passing the microbiological standard. Novelty impact statement: Inulin and WPC could be used to replace fat in cream puff products. Inulin and WPC could extend the shelf life of cream puff products in terms of microbiological and sensory properties. Increasing WPC content more than 10% in filling formulation added undesirable sensory characteristics.